Speciační analýza selenu v kvasinkách kultivovaných v médiu s přídavkem selenu - Motlová, Tereza (Vysoké učení technické v Brně. Fakulta chemická, 2010)
Cílem diplomové práce bylo stanovení specií selenu v kvasinkách Saccharomyces cerevisiae kultivovaných v médiu, do kterého byla přidána anorganická forma selenu (seleničitan sodný). Koncentrace seleničitanu sodného v kultivačním médiu byly 0,1; 1; 10 a 100 mg.l-1. Kultivace byla prováděna ve fermentoru po dobu 72 hodin. Nakultivované obohacené kvasinky byly enzymaticky extrahovány a poté byly stanoveny specie selenu v jednotlivých částech kvasinek. Ke stanovení specií selenu byla použita vysokoúčinná kapalinová chromatografie ve spojení s atomovým fluorescenčním spektrometrem a s technikou generací hydridů. Analýzou různých frakcí kvasinek Saccharomyces cerevisiae bylo zjištěno, že během kultivace dochází k sorpci selenu ve formě Se4+ v buněčných membránách, zatímco v cytoplasmě nebyly anorganické formy selenu naleznuty. Dále bylo zjištěno, že kvasinky Saccharomyces cerevisiae jsou schopny metabolicky přeměňovat anorganické formy selenu na organické formy (selenomethionin), přičemž tyto formy jsou přítomny v cytoplasmě a jsou také pravděpodobně vázány na bílkovinné struktury buněčných membrán. Se zvyšující se koncentrací seleničitanu sodného v kultivačním médiu docházelo k nárůstu koncentrace Se4+ v buněčných membránách. V bílkovinných strukturách buněčných membrán se koncentrace organických forem selenu zvyšovala pouze do koncentrace 10 mg.l-1 seleničitanu sodného v kultivačním médiu.

The aim of the theses was determination of selenium species in yeast Saccharomyces cerevisiae cultivated in medium with added inorganic form of selenium (Sodium Selenite). Concentrations of Sodium Selenite in cultivation medium were 0,1; 1; 10 and 100 mg.l-1. Cultivation was undertaken in fermenting tub for period of 72 hours. Cultivated yeasts were extracted by use of enzymes and subsequently the species of selenium in particular parts of yeasts were determined. In order to determine selenium species, the method of high-performance liquid chromatography in combination with atomic fluorescent spectrometer and technique of hydride generation was used. Having analysed different fractions of the yeasts Saccharomyces cerevisiae it was ascertained that during cultivation the sorption of selenium occurred in form of Se4+ in cell membranes while in cytoplasm no inorganic forms of selenium were found. Furthermore, it was stated that yeasts Saccharomyces cerevisiae are able to metabolically change inorganic forms of selenium to organic forms (selenomethionine), while these forms are present in cytoplasm and they are likely to be bound to proteinic structures of cell membranes. An increase of concentration of Se4+ in cell membranes could be observed as a result of increasing concentration of Sodium Selenite in cultivation medium. In proteinic structures the concentration of organic selenium forms increased only to concentration 10 mg.l-1 of Sodium Selenite in cultivation medium.
Speciation analysis of selenium in selenized yeast
Keywords: selen; speciační analýza; kvasinky; vysokoúčinná kapalinová chromatografie (HPLC); generace hydridů (HG); atomová fluorescenční spektrometrie (AFS); extrakce; Selenium; speciation analysis; yeast; high performance liquid chromatography (HPLC); hydride generation (HG); atomic fluorescence spectrometry (AFS); extraction